Diverse Cooperative Field Membership and Small-Scale Producers' Access to Certification. Issue 2 (2nd April 2020) - Nguyen, Tram Anh Thi; Jolly, Curtis M.
Abstract: The research investigates whether cooperative formation through horizontal integration is best way forward to enable small-scale farmers meet certification requirements. The study employed a literature review on the shrimp industry in Vietnam, value chain analysis, cooperative formation through horizontal integration while developing vertical integration linkages with larger lead firms plus a case study review to investigate the survivability of small-scale farmers under standards imposition by importers. The study is based on theoretical concepts and on a case study. The study showed that the formation of a cooperative is a necessary condition to assist small-scale farmers to access certification. Formation of a cooperative with a diverse field of membership including small-scale farmers, collectors, and providers of supporting logistics to the value chain, as well as vertical backward integration with input providers and vertical forward integration with processing plants, are sufficient conditions to enable small-scale producers to attain certification and improve product standards. The study investigates the importance of cooperative formation through horizontal integration as a practical solution to enable small-scale shrimp producers to survive the severe standard requirements by importers. The study implies that social gatherings such as cooperatives can be used for knowledge transmission to enable small-scale farmers survive the standard requirements by importers. The study is original in its combination of horizontal integration for forming cooperatives with diverse field of membership and vertical integration with large firms to circumvent the pressures of standards by shrimp importers. Additional data from functional cooperatives would have to verify further the findings.